An Analysis Of 21st Century EFL Teachers’ Pedagogical Competence Regarding The Digital Era - Meifauziah, Ulfatunisa; Said, Ishak (Journal of English Education Program (JEEP), 2024)
Teachers and students in the 21st century must be able to communicate, to adapt, and to keep up with the digital technology which characterized by the development of technology. It is inevitable that a teacher must be able to have a continual improvement in learning methods. This study aimed to analyze the 21st-century EFL teachers’ pedagogical competence regarding digital era. In particular, the study is aimed to find out 1) EFL Teachers’ perspective toward 21st-century teaching competence; and 2) the way the EFL teachers develop their 21st-century teachers’ pedagogical competence regarding the digital era. This research uses a qualitative case study design which was conducted in a school at Malangbong. The participants of this study were EFL Teachers 10 at a school in Malangbong who were chosen by using the convenience sampling technique. To collect the data, the researcher combined the data obtained using an open-ended questionnaire and interview. The result of this study showed that the pedagogic competence of 21st-century teachers is very much needed because 21stcentury pedagogic competence is very beneficial for teachers and students. Teachers can be more creative in facilitating learning in this era because the 21st century is certainly related to technology and of course with the increasing pedagogic competence in the 21st century. Therefore, teachers must become facilitators and an inspiring teacher for students to maintain a positive classroom atmosphere.